Education for Self-Fulfillment: process and context - Robert A. Stebbins (Universidade Federal do Rio Grande do Sul, 2016)
Education gained through leisure activities plays a central role in our search for self-fulfillment, be the leisure activity a project or a serious pursuit. After discussing the serious leisure perspective, education, both formal and informal, is explored for its special contribution to fostering fulfillment, defined as the realization of personal tastes, talents, and potential. Several key concepts marking the road to fulfillment are discussed: life course, process, leisure education, adult education, self-directed learning, and experience. The ways that acquired education as background knowledge is applied constitute a crucial step in finding self-fulfillment in an activity. The role of Internet and digital technology is also examined.